Impact of the introduction to special education course in improving attitudes among handicapped individuals - Khalid Mohammad Aljundi (Intelektual Pustaka Media Utama, 2022)
The present descriptive study aimed to survey the Faculty of Education students’ attitudes to handicapped individuals in Jordan, in a bid to explore the need for programmes to change negative attitudes to this group. The population of the study consisted of all the 123 students who registered in the introduction to special education course in the summer course in the academic year 2021-2021 or the first semester of the academic year 2021-2022 among bachelor’s degree majors of the Faculty of Education at the Arab Open University/Jordan. The sample of the study consisted of 57 students, who were selected at random of the population. The tool applied was that developed by Al-Qureiti for students’ attitudes to handicapped individuals, which was adapted for Jordan’s environment by Darwish. It consisted of 60 paragraphs of three sections on different aspects. On the other hand, arithmetic mean, standard deviation, T-test and one-way analysis of covariance (ANCOVA) are adopted. It is found that there are statistically significant differences at 0.05≥α attributed to taking the course. There are similar statistically significant differences related to the gender factor, as female are shown to have more positive attitudes than male.